2012
DOI: 10.1177/1753193412454252
|View full text |Cite
|
Sign up to set email alerts
|

High frequency failure of the Moje thumb carpometacarpal joint arthroplasty

Abstract: Arthroplasty is one of several options for treating symptomatic osteoarthritis of the thumb carpometacarpal joint. There are various hemi- and total arthroplasties available on the market. We report our experience of treating 12 patients with the Moje Acamo CMC1 prosthesis. We reviewed all the patients at a mean of 50 months postoperatively. All patients presented with loosening, migration or tilting of one or both implant components. Nine patients were symptomatic enough to warrant revision surgery with remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 24 publications
2
37
0
2
Order By: Relevance
“…Following failed Moje CMC joint arthroplasties, excision of the implant gives results comparable to a primary trapezectomy (Kazsap et al, 2012). Nonetheless, the reported failure rates of the CMC joint arthroplasties are vastly greater than the "unacceptable" failure rates of some metal-on-metal hip replacements, and yet they continue to be implanted.…”
Section: Editorialmentioning
confidence: 91%
See 1 more Smart Citation
“…Following failed Moje CMC joint arthroplasties, excision of the implant gives results comparable to a primary trapezectomy (Kazsap et al, 2012). Nonetheless, the reported failure rates of the CMC joint arthroplasties are vastly greater than the "unacceptable" failure rates of some metal-on-metal hip replacements, and yet they continue to be implanted.…”
Section: Editorialmentioning
confidence: 91%
“…Previously, Hanson and Vainorius (2008) reported a failure rate of eight out of nine implants at 1 year, primarily due to failure of implant fixation to bone. In this issue, Kazsap et al (2012) also report a similarly high rate of failure, specifically with 75% of implants requiring or being recommended revision surgery.…”
Section: Editorialmentioning
confidence: 98%
“…While initial results seemed favorable, longer-term studies of some initially successful implants have shown an increasing incidence of prosthetic failure requiring revision [1,21]. The dearth of reports of new prosthetic designs in the more recent literature would seem to reflect a shift away from this approach while, during the same period, there continue to be reports introducing new modifications of resection arthroplasty [19,36].…”
Section: Perspectivementioning
confidence: 93%
“…There continue to be advocates for prosthetic arthroplasty using various designs [6,30,31,38], with reports of good clinical results including, for one design, a 5-year survival rate of 95% [10]. Most current reports are from European surgeons [21,22,31], a consequence of the difficulty in obtaining FDA approval for many of the newer biomaterials and designs. A prosthetic implant may be a reasonable salvage procedure when a resection arthroplasty procedure fails.…”
Section: Future Evolution: Addressing Key Issuesmentioning
confidence: 99%
“…[91][92][93][94] When combined with an STT arthrodesis for treatment of pantrapezial osteoarthritis, loosening was observed in most cases. [96][97][98][99][100][101][102] As with other joints in the hand, the initial experience of 1st CMC joint arthroplasty was with silicone implants. 94 Cemented implant designs appear more successful for basal thumb arthritis than uncemented equivalents, with high rates of early loosening observed with the Ledoux, Moje and Elektra uncemented ball and socket designs although, as with the cemented arthroplasties, this does not always lead to revision or have a detrimental effect on the outcome.…”
Section: Reported Outcomes: First Carpometacarpal Jointmentioning
confidence: 99%